2007
DOI: 10.1590/s0102-67202007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida do paciente submetido à Microcirurgia Endoscópica Transanal (TEM)

Abstract: InTRODUÇÃOA Microcirurgia Endoscópica Transanal (TEM) foi desenvolvida em 1983 por Gerhard Buess 13 e corresponde a um dos mais recentes avanços no campo da cirurgia minimamente invasiva para o tratamento dos tumores do reto. A TEM proporciona o tratamento de lesões retais selecionadas com baixa morbi-mortalidade e resultados semelhantes ao da cirurgia radical convencional.Atualmente, existe a tendência em se avaliar a qualidade de vida pós-operatória nas diversos procedimentos cirúrgicos. Não há qualquer trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The negative were related to pain, fear of the possibility of radical surgery and discomfort in the various examinations and preoperative bowel preparation. All reported that they were fully informed about the nature of the procedure and indicate a friend or family member, even those who had complications such as rectovaginal fistula, temporary bypass and relapse 25 . The concepts of radiation have been changed in recent years with the expansion of the total dose to 45-50 Gy and combination with chemotherapy, which would add the benefit of a synergistic action in order to control any residual tumor after surgery.…”
Section: Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…The negative were related to pain, fear of the possibility of radical surgery and discomfort in the various examinations and preoperative bowel preparation. All reported that they were fully informed about the nature of the procedure and indicate a friend or family member, even those who had complications such as rectovaginal fistula, temporary bypass and relapse 25 . The concepts of radiation have been changed in recent years with the expansion of the total dose to 45-50 Gy and combination with chemotherapy, which would add the benefit of a synergistic action in order to control any residual tumor after surgery.…”
Section: Morbiditymentioning
confidence: 99%
“…Began to be practiced since 1982 in Germany and, currently, is used in major centers. Its introduction in Brazil was due to the first author of this paper in 2002 at the Department of Digestive Surgery, Hospital de Clínicas, Federal University of Paraná in Curitiba, Brazil 20,21,22,23,24,25 . This paper presents the results of a non-random prospective series of patients with early rectal cancer treated by transanal endoscopic microsurgery.…”
Section: Introductionmentioning
confidence: 99%